2007
DOI: 10.1007/s00264-007-0407-9
|View full text |Cite
|
Sign up to set email alerts
|

BMP-6 exerts its osteoinductive effect through activation of IGF-I and EGF pathways

Abstract: We have recently shown that human recombinant BMP-6 (rhBMP-6), given systematically, can restore bone in animal models of osteoporosis. To further elucidate the underlying mechanisms of new bone formation following systemic application of BMPs, we conducted gene expression profiling experiments using bone samples of oophrectomised mice treated with BMP-6. Gene set enrichment analysis revealed enrichment of insulin-like growth factor-I and epidermal growth factor related pathways in animals treated with BMP-6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…It is known that BMPs support differentiation of C2C12 cells towards an osteoblastic phenotype [51,52]. BMP6 in concentration of 50 ng/ml induced the expression of ALP by 180-fold and OC by four-fold after 72 h. The addition of heparin (10 μg/ml) attenuated the expression of both osteoblastic markers, which is also consistent with previous reports demonstrating that exogenous heparin can inhibit BMP2 and BMP7 binding to their receptors [10,15].…”
Section: Discussionsupporting
confidence: 80%
“…It is known that BMPs support differentiation of C2C12 cells towards an osteoblastic phenotype [51,52]. BMP6 in concentration of 50 ng/ml induced the expression of ALP by 180-fold and OC by four-fold after 72 h. The addition of heparin (10 μg/ml) attenuated the expression of both osteoblastic markers, which is also consistent with previous reports demonstrating that exogenous heparin can inhibit BMP2 and BMP7 binding to their receptors [10,15].…”
Section: Discussionsupporting
confidence: 80%
“…To elucidate the underlying mechanism, gene expression profiling experiments revealed enrichment of IGF-1 and EGF related pathways in rats treated with BMP6. Similar results were obtained on primary human osteoblasts, suggesting that BMP6 exerts its osteoinductive effect, at least in part, through IGF-1 and EGF pathways [13]. In C2C12 premyoblasts, alteration of the plasma membrane heparan-sulfate (HS) structures with chlorate or heparinase III treatment inhibited BMP6-mediated signaling and differentiation of the cells into osteoblasts, indicating that endogenous HS plays an important role in the BMP6 activity.…”
Section: Osteogrow: a New Bone Device Consisting Of Bmp6 And A Biocomsupporting
confidence: 67%
“…Functional analysis demonstrated that PDGF-BB stimulated osteoblast chemotaxis that was reduced by assessing siRNAs of PDGFR-β in osteoblasts [10,11]. Growth factors released during bone resorption that rebound to the extracellular matrix components also include transforming growth factor β1 (TGFβ1) and insulin growth factor 1 (IGF-1) [12], stimulating osteoblast differentiation from bone marrow mesenchymal stem cells (BMSCs) [13,14]. A novel molecule named couplin has been recently identified in osteoclasts that also promotes osteoblast differentiation from BMSCs.…”
Section: Molecular Mechanisms Of Bone Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, using gene expression profiling, we found that BMP-6 exerts its osteoinductive effect at least in part through the IGF-I and epidermal growth factor (EGF) pathways. (Grasser et al, 2007 have studied impairment of osteoblasts differentiation in context of the glucocorticoid-induced osteoporosis. They treated MC3T3-E1 cells with high dose of dexamethasone, which inhibited cell differentiation and proliferation and induced apoptosis.…”
Section: Bone and Cartilagementioning
confidence: 99%